Crystallization and natural aging of thin films produced by pulsed laser evaporation of rhenium - Bagmut, A.G.; Bagmut, I.A.; Murav′ev, T.K.; Slabokrug, D.V. (Functional Materials, 2013)
Rhenium thin-film laser condensates have been obtained by pulsed laser evaporation (PLE) and their structure has been investigated. During annealing and natural aging of films the structural transformations have been examined. As a result of pulsed laser evaporation of Re in vacuum and in the oxygen atmosphere at P(O₂) = 10⁻³ Torr on (001) KCl substrates at room temperature, the amorphous films have been formed. Amorphous films become crystalline after annealing. The natural aging in air provides the formation of ReO₃ crystals on the film surface. The formation of crystals took place non-uniformly. The ReO₃-poor and ReO₃-rich crystal zones are formed. The ReO₃ crystalline structure is destroyed during annealing in vacuum. The polycrystalline films consisting of ReO₂ and ReO₃ crystals have been grown as a result of PLE of Re in oxygen atmosphere under P(O₂) = 10⁻² Torr on substrates at room temperature.